Evaluasi Kebijakan Keamanan Siber terhadap Privasi Data Pengguna SIA Digital : Studi Literatur - Alifiya Husna; Cantika Marcelly Pardosi; Yohana Sembiring (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
This study aims to evaluate cybersecurity policies on user data privacy in digital Accounting Information Systems (AIS) through a literature review method. This article uses a literature review from international and national journals over the past 10 years (2015–2025). Data was obtained through Google Scholar and other academic databases using the keywords cybersecurity, accounting information system, and privacy. Of the 45 articles identified, 12 articles were selected as samples for qualitative analysis. The results show that cybersecurity policies play a significant role in maintaining the privacy of digital AIS user data, but still face challenges in terms of user awareness, resource limitations, and regulatory implementation. The main recommendations are strengthening regulations, implementing the latest security technologies, and improving user digital literacy.